In vitro effect of Q-switched Nd:YAG laser exposure on morphology, hydroxyapatite composition and microhardness properties of human dentin - Retna Apsari; Siswanto Siswanto; Anita Yuliati; Noriah Bidin (Universitas Airlangga, 2011)
Background: A Q-switched Nd:YAG laser was employed as a source of ablation. The fundamental wavelength of the laser is 1064 nm, with pulse duration of 8 nanosecond operates with uniphase mode of TEM00. In the following experiments, dentin samples (without caries and plaque) are exposed to pulse laser with Q-switching effect at various energy dose. Purpose: The aim of this study was to investigate the effect of laser ablation on dentin samples using Q-switched Nd:YAG laser exposure. Methods: The laser was operated in repetitive mode with frequency of 10 Hz. The energy dose of the laser was ranging from 13.9 J/cm2, 21.2 J/cm2 and 41.7 J/cm2. The target material comprised of human dentin. The laser was exposed in one mode with Q-switched Nd:YAG laser. Energy delivered to the target through free beam technique. The exposed human dentin was examined by using x-ray diffraction (XRD) and fluoresence scanning electron microscopy for energy dispersive (FESEM-EDAX). Microhardness of human dentin were examined by using microhardness vickers test (MVT). Results: The result obtained showed that the composition of hydroxyapatite of the dentin after exposed by Q-switched Nd:YAG laser are 75.02% to 78.21%, with microhardness of 38.7 kgf/mm2 to 86.6 kgf/mm2. This indicated that exposed pulsed Nd:YAG laser on the human dentin attributed to the phototermal effect. The power density created by the Q-switched Nd:YAG laser enables the heat to produce optical breakdown (melting and hole) associated with plasma formation and shock wave propagation, from energy dose of 21.2 J/cm2. From XRD analysis showed that the exposure of Nd:YAG laser did not involve in changing the crystal structure of the dentin, but due to photoablation effect.